The state of the world's forest biodiversity - Sayer, Jeffrey A.; Iremonger, S. (1998)
The term of biodiversity was first used un specialized conservation circles in the mid -1980's. In the decade that has elapsed it has moved to center-stage on the international agenda. The Convention on Biological Diversity (CBD), adopted at the Rio Summit in 1992 and now ratified by 169 countries, has had a major impact on biodiversity becoming a global concern. A major landmark was the publication of the Global Biodiversity Assessment (Heywood and Watson 1995), which provided a comprehensive account of the status of the world's biodiversity and of the issues confronting its conservation. Subsequently, in 1996 the Sub-sidiary Body for Scientific, Technical and Technological Adivice (SBSTTA), established by the Parties to the CBD, recognized the extreme importance of forests for biodiversity and established priorities for conservation. It recognized the inadequacy of existing systems of protected areas, the potential for improved conservation in managed forests and the need for more research and assessment to underpin forest biodiversity conservation programs. However, concern at a political level is not being matched by practical conservation achievement on the ground. Fewer new protected areas are being established and many exsisting ones are poorly managed. The possibility of conserving significant biodiversity in extensively managed multiple use areas has still to be proven in practice (Terborogugh and van Schaik 1997). The purpose of this article is to attempt to assess the progress that has been made, to identify some of the key problems, and to identify those actions which would yield the greatest benefits for forest biodiversity conservation